Nonalternant Extension of Multiple Resonance Emitter via Palladium-Catalyzed [5+2]-Annulation - Weiwen Zhuang; Waiming Chong; Junzhi Liu (Organic Materials)
Despite the proliferation of multiple resonance (MR) emitters with rigid 1,4-borazine-based skeletons, the straightforward and efficient incorporation of nonhexagonal rings, especially for heptagons, to avoid notorious aggregation-induced quenching effect remains elusive. Here, a green-yellow emitter consisting of two azepines was designed and synthesized via a palladium-catalyzed one-pot twofold [5+2]-annulation reaction with high selectivity and efficiency. The tetrabenzene-fused benzo[1,2-b:5,4-b']bis(azepine) (TBBBA) core induced a highly twisted and dynamically helical rim for the novel MR-skeleton, which reduced Π-Π stacking in the solid state. Moreover, the nonalternant topology facilitated the delocalization of frontier molecular orbitals (FMO) within the twisted geometry, thus achieving red-shifted narrow emission. Our work provides a new synthetic strategy towards nonalternant extension of MR-emitters and gives insights into the electronic effects of multiple azepination on FMO distribution.